Non-Malaria Causes of Fever among under-5 Children with Negative Results for Malaria Rapid Diagnostic Test in South-Western Nigeria. (27th July 2022) - Orimadegun, Adebola E; Dada-Adegbola, Hannah O; Michael, Obaro S; Adepoju, Adedayo A; Funwei, Roland E; Olusola, Fiyinfoluwa I; Ajayi, IkeOluwapo O; Ogunkunle, Oluwatoyin O; Ademowo, Olusegun G; Jegede, Ayodele S; Baba, Ebenezer; Hamade, Prudence; et al.
Abstract: Background: Although the global malaria burden is decreasing, there are still concerns about overdiagnosis of malaria and the danger of misdiagnosis of non-malaria causes of fever. Clinicians continue to face the challenge of differentiating between these causes despite the introduction of malaria rapid diagnostic tests (mRDTs). Aim: To determine the prevalence and causes of non-malaria-caused fever in children in South-Western Nigeria. Methods: Secondary analysis of data obtained to evaluate the effect of restricting antimalarial treatment to positive mRDT children in rural and urban areas of southwest Nigeria. Clinical examinations, laboratory tests for malaria parasites (including thick blood film and mRDT) and bacterial identification were performed on children aged 3–59 months ( n  = 511). The non-malaria group comprised febrile children who had both negative mRDT and microscopy results, while the malaria group included those who were positive for either mRDT or microscopy. We compared the causes of fever among children with non-malaria fever and those with malaria. Results: The prevalence of non-malaria fever and bacteria–malaria co-infection was 37.2% and 2.0%, respectively. Non-malarial pathogens identified were viral (54.7%) and bacterial (32.1%) infections. The bacterial infections included bacteriaemia (2.7%), urinary tract infections (21.6%), skin infections (11.6%) and otitis media (2.6%). The leading bacterial isolates were Staphylococcus aureus, Pseudomonas aeruginosa and Streptococcus pneumoniae . Conclusion: The high prevalence and wide range of non-malarial infections reinforces the need for point-of-care tests to identify bacterial and viral infections to optimize the treatment of febrile illnesses in malaria-endemic areas.